The Potential Customer Duration/Visit Characteristic Based on Traffic Source in a Service Provider Web Site - Prasetio, Adhi; Hatammimi, Jurry (Universitas Brawijaya, Indonesia, 2013)
The purpose of this research is to find out if there are any significant duration/visit difference between potential customers who come from direct, search and referral traffic sources in a service provider web site. Sample data were collected from google analytics then analyzed using descriptive statistic and ANOVA. The result shows that duration/visit from referral is the lowest and direct is the highest compare to other traffic sources.